The Impact of Administrative Empowerment on Institutional Excellence in Public Sector Organization: A Field Study on School Principles in Jeddah - A ALTALHI, ADEL (The Arab Journal of Administration, 2023)
Administrative empowerment and institutional excellence are among the recent topics that have received great attention from researchers in the field of management, and that is because modern organizations have become extremely interested in human resources (managers) as they are the basis of the administrative process. It is an essential component of the organization. This study came to discover the relationship between these two variables: administrative empowerment and institutional excellence. As well as knowing the level of administrative empowerment of the principals of education schools in the General Administration of Education in Jeddah Governorate. To verify the objectives of this study, the descriptive approach was used since it is the most suitable for such studies, and the use of the questionnaire as a tool for data collection. The study reached the following results: There is a statistically significant relationship between administrative empowerment and institutional excellence. There is a low level of administrative empowerment in the schools of the General Administration of Education in Jeddah Governorate. Based on these research results, it will help making executive decisions, formulating, and developing public policies for education and what it will contribute to providing useful information to researchers and scholars for future researchers.